2011
DOI: 10.4314/ajpsy.v14i1.65473
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia among Sesotho speakers in South Africa

Abstract: Objective: The aim of this study is to investigate the clinical presentation of schizophrenia among Sesotho speakers. Method: A sample of 100 participants diagnosed with schizophrenia was evaluated using the Psychiatric Interview Questionnaire. Results: Core symptoms of schizophrenia among Sesotho speakers do not differ significantly from other cultures. However, the content of psychological symptoms such as delusions and hallucinations is strongly affected by cultural variables. Somatic symptoms such as heada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…In three South African studies, Mosotho et al. (), de Wet et al. () and den Hertog & Gilmoor () found that traditional and faith healers were often sought in the first instance.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In three South African studies, Mosotho et al. (), de Wet et al. () and den Hertog & Gilmoor () found that traditional and faith healers were often sought in the first instance.…”
Section: Resultsmentioning
confidence: 99%
“…Mosotho et al. () explored the main symptoms of schizophrenia exhibited by Sesotho speakers attending local mental health hospitals and found that the vast majority consulted both conventional psychiatric services and traditional or faith healers. In a Ugandan study of treatment outcomes for psychosis by traditional healers, Abbo et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, of those who reported persecutory delusions, 72.5% ( n  = 125) believed that others had bewitched them to bring about their mental illness, through evil spirits, “amafufunyana” or the “Tikoloshe”. This bewitchment framework has been reported to influence the content of delusions in other African samples including Sesotho people with schizophrenia from the Free State province of South Africa [Mosotho 40], and in neighboring African countries like Namibia [41], suggesting that this explanatory framework may be common in Southern African cultures. This observation aligns well with epidemiological studies that report the frequent use of spiritual causes as explanations for psychiatric illness in Southern African communities [19].…”
Section: Discussionmentioning
confidence: 98%
“…Traditional beliefs on causation were also common, in line with previous studies showing that attitudes, beliefs and experiences relating to schizophrenia are substantially different in South Africa from Western conceptualisations (Mbanga et al . 2002; Mosotho, Louw & Calitz 2011). Service users’ conceptualisation of their recovery from the illness was characterised by high value placed on engagement in productive activities and the ability to work as reported previously in South Africa by service users and user advocates (Kleintjes, Lund & Swartz 2012; Van Niekerk 2009;).…”
Section: Discussionmentioning
confidence: 99%